PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO KUE RUMAH TALAS BOGOR - Sari, Oktavia (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
The purpose of this study was to determine and analyze the effect of product quality and price on purchasing decisions at the Rumah Tala Bogor cake shop. The type of research used is survey research with research methods in the form of data collection using questionnaires. The data analysis model used is multiple linear regression analysis. The sample selection was carried out by distributing questionnaires to consumers who had shopped at Rumah Talas Bogor. The sempel amounted to 100 respondents. The results of the regression test show that 41.3% Simultaneously product quality and price have a significant effect on purchasing decisions at the Rumah Talas cake shop, Bogor. Partially, product quality has a significant effect on purchasing decisions at the Rumah Talas cake shop, Bogor. And partially the price has a significant effect on purchasing decisions at the Rumah Talas Bogor cake shop. Based on the results of the analysis that has been done before, it can be seen that product quality has a tcount of 4.616 with a significance of 0.000, it can be concluded that the product quality variable has a positive and significant effect on purchasing decisions. And the results of the price variable have a tcount of 3.850 with a significance of 0.000, it can be concluded that the price variable has a positive and significant effect on purchasing decisions